The Molecular Clock Mediates Leptin-Regulated Bone Formation - Fu, Loning; Patel, Millan S.; Bradley, Allan; Wagner, Erwin F.; Karsenty, Gerard (Cell, 2005)
The hormone leptin is a regulator of bone remodeling, a homeostatic function maintaining bone mass constant. Mice lacking molecular-clock components ( Per and Cry), or lacking Per genes in osteoblasts, display high bone mass, suggesting that bone remodeling may also be subject to circadian regulation. Moreover, Per-deficient mice experience a paradoxical increase in bone mass following leptin intracerebroventricular infusion. Thus, clock genes may mediate the leptin-dependent sympathetic regulation of bone formation. We show that expression of clock genes in osteoblasts is regulated by the sympathetic nervous system and leptin. Clock genes mediate the antiproliferative function of sympathetic signaling by inhibiting G1 cyclin expression. Partially antagonizing this inhibitory loop, leptin also upregulates AP-1 gene expression, which promotes cyclin D1 expression, osteoblast proliferation, and bone formation. Thus, leptin determines the extent of bone formation by modulating, via sympathetic signaling, osteoblast proliferation through two antagonistic pathways, one of which involves the molecular clock.